Internal erosion by suffusion on cohesionless gap-graded soils: Model and sensibility analysis. (September 2022) - Gelet, Rachel; Marot, Didier
Abstract: Cohesionless gap-graded soils are susceptible to volumetric internal erosion, also called suffusion, under the action of seepage flow through the porous material. More precisely, during suffusion three processes simultaneously take place: detachment, transport and possible filtration of the fine particles. This paper proposes a new relationship to describe the development of suffusion based on the energy approach. The proposed relationship is a power law that relates the volumetric cumulative eroded mass with the volumetric cumulative energy dissipated by the flow. This law requires three material parameters: the erosion resistance index and the maximum volumetric cumulative energy that both characterize the fully-eroded state; and a smoothing time that controls the suffusion kinetics. The first two parameters are being measured from a series of experimental tests performed in oedometric conditions. The experimental program was set up to study suffusion development on three different soils and along three seepage lengths. The erosion resistance index was found to be insensitive to the seepage length. On the other hand, the maximum volumetric cumulative energy tends to increase with the seepage length. This increase is being attributed to the transport and filtration phenomena. The cumulative eroded mass predicted by the energy-based relationship compares reasonably well with the experimental data, by fitting for each test a fixed smoothing time. To improve our physical understanding of the suffusion kinetics, a relationship between the smoothing time and the hydraulic diffusion time is postulated in accordance with experimental observations. Such hypothesis improves the cumulative eroded mass predictions. Highlights: A new approach to compute suffusion development is proposed based on the stable state of suffusion. Suffusion experimental tests are realized in oedometric conditions on three different soils and along three seepage lengths. The predicted suffusion development compares reasonably well with experimental data.